PENGGUNAAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) SEBAGAI UPAYA UNTUK MENINGKATKAN MINAT DAN KEMAMPUAN PEMAHAMAN KONSEP GARIS DAN SUDUT PADA SISWA KELAS VII MTS. PUTRA NURUL HAKIM KEDIRI TAHUN PELAJARAN 2012/2013 - HARDIAWAN HARDIAWAN (Lensa: Jurnal Kependidikan Fisika, 2013)
The mathematics lesson in class VII MTs Putra Nurul Hakim Kediri is less desirable by the students. Therefore, their understanding of mathematical concepts is lacking. This study aims to apply Contextual Teaching and Learning (CTL) model to improve students' interest and understanding ability. The results showed that, the evaluation of cycles I and II, the percentage of classical completeness are: 66.66% and 87.87%. Teacher activity is good in cycle I and II. Students' math learning interest is very high in cycle II. The results of this study indicate an increase in interest and ability to understand students' concepts. We conclude that the Contextual Teaching and Learning (CTL) model proves to increase students' interest in and understanding of concepts.